Revisiting the poorly known Chilean genus Autostreptus Silvestri, 1905 (Diplopoda, Spirostreptida, Spirostreptidae) with the description of a new species - Antonio Parra-Gómez; Luiz F.M. Iniesta; Jesús A. Morales (European Journal of Taxonomy, 2025)
The genus Autostreptus Silvestri, 1905, endemic to Chile, is revisited here with the description of Autostreptus silvagonzalezi sp. nov., and redescriptions of A. chilensis (Gervais, 1847) and A. yanezi Demange & Silva, 1971, based on freshly collected material. Pictures of general somatic and male sexual characters of all species are provided, and descriptions of secondary sexual characters are presented for the first time. Additionally, notes on the taxonomic assignment of the genus to the tribe Perustreptini Verhoeff, 1941 and novel records of A. chilensis and A. yanezi are included.